The impact of posture and basking orientation on thermoregulation in the Sungazer (Smaug giganteus). (July 2018) - Stanton-Jones, Wade K.; Parusnath, Shivan; Alexander, Graham J.
Abstract: Body temperature (Tb ) is one of the most influential factors affecting physiological processes in ectothermic animals. Reptiles use behaviours such as shuttling, and postural and orientation adjustments to ensure that Tb remains close to a target. It is thought that target body temperature (Ttarget ) is aligned to the physiological and behavioural thermal optima of the animal. The Sungazer ( Smaug giganteus ), a Threatened lizard species, is unique amongst the Cordylidae in that lizards inhabit self-excavated burrows in open grasslands, a habitat in which there are few exposed rock basking sites. In this situation, Tb s are likely to be greatly influenced by postural and orientation adjustments during basking. We measured Tb s using modified iButtons, and calculated Ttarget of free-ranging Sungazers in order to assess the impact of body posture and orientation in the thermoregulation of the species. We used camera traps to record lizard behaviour at burrow entrances and aligned these measures to measures of Tb . Ttarget was 30 ± 1.4 °C, and Tb s remained within this range for 371 ± 162 min per day. The anterior body-up postures resulted in faster heating and higher Tb s. Lizards heated faster when facing away from the sun and spent proportionally more time in this orientation in the morning when Tb s were lower than Ttarget . Our findings suggest that their wide behavioural repertoire allows Sungazers to thermoregulate effectively over a broad range of environmental conditions and may thus be able to effectively respond to changing climatic conditions. Highlights: Sungazers achieve a target body temperature of 30 ± 1.4 °C. The anterior body-up postures result in faster heating. Sungazers heat faster when facing away from the sun. Body posture, early morning basking, and maximized surface area exposure positively impacts Sungazer thermoregulation.